THE SYSTEM STATUS CONTROL USING THE SWITCH ENGINES ON THE CURVE OF THE CURRENT CONSUMPTION IN MAINTENANCE AREAS - Malovichko, V. V.; Havryliuk, V. I.; Reshetniak, M. I. (Science and Transport Progress, 2007)
The analysis of existing method of verification of pointer engines of direct current with the successive excitation in the repair-technical areas has been conducted, the automated device for the exposure of refusals in the electric engines on the curves of consumption of current in the conditions of repair-technical areas at the periodic examination has been offered.